The TED Talks Application as a Learning Tool in Teaching Spaking - Indah Sari, Mutiara; Hadi, M. Sofian; Mutiarani, Mutiarani (Universitas Nusantara PGRI Kediri, 2021)
The aim of this study is to improve the learning of English with a speech variable using the TED Talks Application. The quantitative approach is the technique used in this research. The design used in this quantitative study is a quasi-experimental design, which utilizes a pre-test and post-test design culture. The population in this study was 20 grade XII students of SMK Muhammadiyah Parung, Bogor in the academic year 2020/2021. Pre-test and post-test data were analyzed using SPSS 25 version. The results of the study showed that the students pre-test score was 64.70 and after treatment, the students post-test score was 87.60. The results of this study also clarified that the t-test in the paired sample test in which tobtained was 28.56 and the crucial tvalue at significance level (p)=0.05 was 2.093, which means that t-test in which the null hypothesis (Ho) was rejected and the alternative hypothesis (H1) accepted. The writer finding might summarize that the student’s post-test results are higher than the student’s pre-test results. In other words, the use of TED Talks is useful in the 12th grade of vocational high school for students who speak English.